Preliminary Phytochemical and Biological Screening of Cyclamen coum a Member of Palestinian Flora - Nidal Amin Jaradat, Motasem Al-Masri, Fatmeh Hussen, Abed Naser Zaid, Iyad Ali, Ala Tammam, Doaa Mostafa Odeh, Omaima Hussein Shakarneh, Areej Rajabi (Tabriz University of Medical Sciences, 2017)
Background: Since ancient times, the treatment of various diseases has relied on medicinal plants. The replacement of chemically synthesized drugs with natural medications gave the later advantageous due to their safety for humans. This study aimed to screen and to evaluate preliminarily phytoconstituents, total contents of flavonoids, tannins, and phenols also to evaluate the antibacterial and antioxidant activities of Cyclamen coum aerial parts methanol extract. Methods: Screening of phytoconstituents, total flavonoids, tannins and phenols contents, as well as antioxidant properties, were investigated for the Cyclamen coum aerial parts by using standard phytochemical and analytical methods. Evaluation of antibacterial activity of the plant methanolic extract was performed by using broth microdilution method. American Type Culture Collections of Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Methicillin-Resistant Staphylococcus aureus (MRSA) were utilized to evaluate antibacterial activity. Results: Preliminary phytochemical qualitative analysis of the plant methanolic extract showed that the plant aerial parts contained amino acids, reducing sugar, carbohydrate, tannin, flavonoid, phenol, saponin, cardiac glycoside, and steroids. Total flavonoids, phenols, and tannins in plant methanolic extract were 60.88 mg QUE/g, 32.7 mg GAE/g and 11.7 mg CAE/g, respectively. Meanwhile, the antioxidant activity was estimated to be 31 µg/mL and has very weak antibacterial activity on the studied pathogens. Conclusion: In the present study, evaluation of total phenolic, tannins and flavonoid content from the aerial parts of C. coum can be an antioxidant naturally potent source. The results of in-vitro antibacterial studies showed that the studied plant has very weak antibacterial activity. In addition, the presence of antioxidant compounds in C. coum makes it a good candidate for manufacturing dietary supplements and food preservatives